Halal Product Assurance at Traditional Markets in Luwu Raya Based on Halal Supply Chain Traceability - tahmidnur, muhammad; Ishak, Ishak; Rusmana Putri, Qisty Amalina; Sarijuddin, Peni (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2024)
The purpose of this study is to explore halal products in the Greater Luwu Market using halal supply chain treacebilit. the research intends to develop practical guidelines and recommendations for market operators and regulators to implement and maintain Halal assurance systems effectively. Ultimately, the goal is to promote consumer confidence in Halal products available in these traditional markets and contribute to the broader objective of standardizing Halal practices in the region. This study uses qualitative research by collecting data in the form of random interviews with economic actors of producers, distribution, and consumers in the Greater Luwu market. The results of the study found that first there are three sources of supply of goods or commodities in the Greater Luwu Market, namely outside the city , collectors of goods and land products themselves. Secondly, the application of halal awareness indirectly in the Greater Luwu community, which in fact is mostly Muslim, makes halal supply management in the Greater Luwu market run according to the provisions even though there is no specific tool to detect supply, so that the availability of halal food ingredients in the Greater Luwu market can be said to be easy to find and still dominant.